MILLENNIALS INVESTMENT DECISION ON INDONESIA GOVERNMENT SUKUK: AN ANALYSIS USING BEHAVIOURAL FACTORS - Irfan Hassandi (Jurnal Bisnis dan Manajemen (JBM), 2024)
Sharia products are well-developed in the Indonesian market. The growth of Sharia products in Indonesia caused not only the benefits but also the growth of the population in Indonesia, especially the Muslim population. One of the Sharia products published by the Indonesian government is Sukuk. The government uses Sukuk to fund its expenditures, such as infrastructure. Indonesia's population pyramid determines that the dominant population in Indonesia is between 20-40 years old and classified as millennials. With psychological factor analysis, this research has purposed to measure what psychological value determines millennials' investment decisions in Government Sukuk products. The results show that variables that have a significant relationship with investment decisions are trait anger, overconfidence, and self-monitoring. Keywords: Government Sukuk; Investor Decision Analysis; Millennials; Behavioural Factors Abstrak Produk syariah berkembang dengan baik di pasar Indonesia. Pertumbuhan produk syariah di Indonesia tidak hanya disebabkan oleh manfaat yang ditawarkan, namun juga pertumbuhan jumlah penduduk di Indonesia, khususnya populasi umat Islam. Salah satu produk syariah yang diterbitkan oleh Pemerintah Indonesia adalah Sukuk. Sukuk digunakan oleh pemerintah untuk mendanai pengeluaran mereka seperti infrastruktur. Piramida penduduk Indonesia menunjukkan bahwa dominasi penduduk di Indonesia adalah kelompok umur antara 20-40 tahun yang tergolong generasi milenial. Dengan analisis faktor psikologis, penelitian ini bertujuan untuk mengukur faktor psikologis yang menentukan keputusan investasi generasi milenial pada produk Sukuk Negara. Hasil penelitian menunjukkan variabel yang mempunyai hubungan signifikan terhadap keputusan investasi adalah trait anger, overconfidence, dan self-monitoring. Kata Kunci : Sukuk Negara, Analisis Keputusan Investasi, Millenial, Faktor Perilaku